From The History Of The Fate Of The Cultural Heritage Of Turkestan (As An Example The Period Of Russian Empire) (Zien Journal of Social Sciences and Humanities, 2025)
The article covers the occupation of Turkestan by the government of the Russian Empire and the looting of rare manuscripts and archival documents of the Uzbek people. In addition, it has been scientifically shown that many Oriental manuscripts, archives of the Khiva and Kokand khanates were confiscated from the libraries of princes’ palaces, madrasahs and mosques in Turkestan and taken to Russian scientific centers.